زیارت قبر رسولﷺ،جمہور اور شیخ ابن تیمیہ: Sheikh Ibn-e-Taymiyyah’s Distinction on the issue of the traveling to visit the tomb of the Holy Prophet ﷺ - Fazal Haq, Muhammad (Al-Amīr Research Journal for Islamic Studies, 2021)
Shaykh-ul-Islam Ahmad bin Abdul Haleem alias Ibn Taymiyya (661-728 AH) is one of the great personalities whose far-reaching effects of his thoughts and opinions have been felt in every age. The issues, on which Allama Ibn Taymiyya has a different opinion, are the result of his such research as well as liquidation, wisdom, Ijtihad and continuous consideration as well as deliberation which have been based on Quran and Sunnah, the interaction of companions and speculation. In his Ijtihadi issues, there is a collection of evidence and proofs related to the Quran and Sunnah. Most of Ibn Tamiya’s dissent is of a jurisprudential and principled nature. Some of these dissents are against the consensus of the Ummah. Some are against the religion of the four Imams, some differences are contrary to Hanbali School of thought itself and some differences are against the majority of scholars. Allama Ibn Taymiyya also has such differences in which he looks unique and distinguished from the whole Ummah. One of them is related to the pilgrimage to the tomb of the Holy Prophetﷺ. According to Islamic scholars, traveling to visit the tomb of the Holy Prophet Muhammad ﷺ is permissible and rewarding. The majority of scholars agree on this. Ibn Tamiya’s position and the difference is that if he did not intend to offer prayers in the Holy Prophet’s Mosque during this pilgrimage, then it is not permissible according to most of the scholars and imams, nor has it been commanded. According to the command of the Holy Prophet ﷺ, the reason behind this is that only three mosques should be packed, namely Masjid al-Haram, Masjid al-Nabawi, and Masjid al-Aqsa. After the Prophet of Islam, there is room for disagreement with the words and deeds of everyone in Islamic thought. Almost all the great scholars have disagreed with this position and have refuted it with arguments. But their other religious and national services cannot be ignored based on this distinction. In the article under discussion, Ibn Tamiya’s position and his arguments will be critically examined in light of the views of other scholars of the ummah.